The Author’s Desire Manifested in Bob Dylan’s Song Lyric entitled “Knocking On Heaven’s Door” - Uci Elly Kholidah (LITERA KULTURA : Journal of Literary and Cultural Studies, 2023)
“Knocking On Heaven's Door” is a song by Bob Dylan written in 1973. This song is unique because it was created after Dylan's mysterious accident in 1966 and that accident put him on hiatus for some time. After returning, there were changes in his works; so the researcher thought there were things related to Dylan's psychological side. This research used the psychoanalytic theory proposed by Jacques Lacan. In analyzing the lyrics of “Knocking On Heaven's Door”, the researcher finds that Bob Dylan as the lyricist is a subject of lack and that lack brings the desire to him. Dylan has a desire for self-authenticity. Thus, it can be concluded that the lyrics of “Knocking On Heaven's Door” are metaphors and metonyms from Bob Dylan's life. Keywords: song lyric, lacan, bob dylan, desire, 'I'.